Synthesis and characterization of clay filled polysulfone membran: the effect of composition and calcination of clay - Amilia, Linggawati; Lang, Dorothea; Mohammad, Abdul Wahab (2004)
A clay mineral is a potential candidate for the filler of molecular composite since it is a compound of layer silicate. The factors that would have to be considered in choosing clay as filler were cost, availability, physical properties, thermal stability, and chemical resistance. In this paper we attempted to synthesize membrane from polysulfone (PSF), polyethyleneglicol (PEG), N.N-dimethyl acetamide (DMAc) and clay, as main polymer, additive, solvent, and filler respectively. Clay used were from South Lampung, Indonesia, which were identified by XRD; consist of montmorillonite, chabazite, and cliptonilolite. Compositions of dope solution were 4.5 g PS, 4.5 g PEG, 14 g DMAc, while that of clay were 3, 4, 5, and 6 w % PSF. Calcinations temperature were 300, 350, 400 and 450 0C. Membrane was found to be in micro filtration, range with percent rejection of dextran T 500 were 30-48% with permeation of 45.76- 642.18 Lm-2h-1atm-1 for pure water flux and 12.80-501.71 Lm-2h-1atm-1 for dextran T 500, respectively. Composition of Clay 4 wt.% PSF without calcination gave the best properties of membrane.